Spontaneous intestinal haematoma associated with neurofibromatosis type-1. (23rd August 2013) - Hassan, Syed; Yee, Victoria; Amer, Syed; Alkhatib, Yaser
Abstract : Vasculopathy in patients with neurofibromatosis-1 are rare but serious and have potentially life-threatening complications. It mostly involves the thoracic, abdominal and intracranial vessels. In this case study we describe the first reported case of spontaneous intestinal haematoma in a young male patient. The first episode occurred at the age of 30, following which 2 years later the second episode was noted at the same anatomical site, which was spontaneous without any inciting event.